Annual performance variation of an EGS power plant using an ORC with NDDCT cooling. (25th July 2016) - Duniam, Sam; Gurgenci, Hal
Highlights: Analysis of ORC powered by enhanced geothermal system with NDDCT cooling. Annual performance variation analysis using coupled NDDCT and cycle model. Typical daily range of net power is ±11%. Typical change in mean daily net power for consecutive days is 3%, can be up to 20%. Abstract: The purpose of this paper is to model an Enhanced Geothermal System (EGS) power plant using an Organic Rankine Cycle (ORC) cooled by a Natural Draft Dry Cooling Tower (NDDCT) and to investigate the influence of the variation of performance of the NDDCT due to changing ambient temperature on cycle performance. The ORC used in this work is the supercritical butene recuperated ORC. The EGS heat source conditions used are those found at the Habanero 1 MW pilot plant in South Australia, with geothermal brine inlet temperature of 220 °C, minimum brine temperature of 80 °C, and brine mass flow rate of 35 kg/s. A one dimensional NDDCT model was developed and integrated into the cycle model, enabling a novel method of coupled analysis of ORC and NDDCT interdependence, which allows analysis of plant performance for varying ambient temperature. The analysis finds that annual average W ̇ net is 2.82 MWe, the typical daily range of W ̇ net is 0.62 MWe (±11%), the typical change in W ̇ net, mean for consecutive days is 0.07 MWe (3%), and the largest is 0.5 MWe (20%). The maximum range at any given time throughout the year, based on historical temperature data extremes is ±31%, but the typical expected range ±10%.